Passing the three gates : interviews with Charles Johnson - Johnson, Charles, 1948- (Book collections on Project MUSE., 2004)
"Jim McWilliams has gathered here the most significant of Charles Johnson's many interviews in a chronological progression, giving an invaluable account of Johnson's development from the late 1970s until the early years of the twenty-first century. The interviews bring up many essential elements of Johnson's life and work: his religious development from the AME Church to Buddhism; the importance to him of family; his emergence out of the civil rights and black power movements, and how his writing responds to both; the importance of his relationship with his mentor John Gardner and his own work as a teacher of creative writing; his interest in phenomenology and philosophical fiction